Sun Tzu: The Art of War and 21st Century Curriculum Development – What can the early Asian philosopher tell us about developing curriculums in the 21st Century? - Walden, Joseph L. (Advances in Social Sciences Research Journal, 2020)
The Art of War was written by Sun Tzu around 512 BC. Sun Tzu’s book focused on military strategy. However, looking the guidance from Sun Tzu can be adapted to curriculum development. This paper uses the words of Sun Tzu from a curriculum development perspective. With a curriculum development perspective, Sun Tzu provides some good guidance on preparing for, conducting and implementing curriculum reviews in order to keep the offerings to the students current and relevant.